Statement by the Managing Director to the International Monetary and Financial Committee on the Fund's Policy Agenda. (Policy Papers; Policy Paper ;, 2010)
Although the global recovery continues to move ahead, it remains fragile and uneven, with continued high unemployment. Many countries are emerging from the crisis with high debt burdens, low growth, and still fragile financial sectors. At the same time, economic activity in many emerging market countries has picked up, attracting large capital inflows that challenge economic policy. Important steps have been taken to make financial sectors safer around the world, but the unfinished agenda is still substantial, particularly for cross-border finance and macro-prudential regulation. All this suggests serious vulnerabilities and challenges remain, requiring continued policy cooperation and collaboration.